The effect of 8-week fast strength training on mixed martial athletes and boxers - Kaya, O.; Gül, G. (European Journal of Physical Education and Sport Science, 2025)
Objective: The aim of this study was to investigate the effect of 8-week explosive strength training on competitive MMA athletes and Boxers. Subjects were of mean age 22.63±5.45 years, and the experience of training mean 10.40±2.62.